"Some things are better left unknown:" The political disclosure of young adults to their parents during the 2017 presidential election in South Korea. Issue 2 (19th August 2021) - Paik, Jihyun Esther
Abstract : This study investigated whether and how young adults disclose their political views to a parent who supports a candidate from an opposing party during election season. Using politeness theory, the study identified predictors of young adults' political disclosure decisions and the amount of face‐saving efforts they will make during the disclosure to influence the voting of their parent. How their face‐saving efforts predict strategic attitude disclosure and postdisclosure outcomes was also examined. An online survey was administered to 176 South Korean young adults 10 days before the 2017 presidential election. Results showed that frequent political talks in a parent–child dyad predicted more disclosure attempts. Consistent with politeness theory, an increased perception of power difference in the parent–child relationship predicted more face‐saving efforts made by young adults for their parent. Contrary to politeness theory, a greater political difference in the parent–child relationship was associated with fewer face‐saving efforts. Parental solicitation of disclosure moderated the effect of power difference in an unexpected way; young adults made more face‐saving efforts for their parent who was perceived to have more power over them and have solicited a political disclosure. Young adults presented an attitude toward the parent's preferred candidate more favourable than the actual attitude. Despite the compromised truthfulness, more face‐saving efforts were associated with a perceived narrowing of the political difference and an increased willingness to engage in political talk with the parent in the future. The findings are discussed from psychological and societal perspectives, with implications for cross‐cutting political conversations.